TRANSITION CHARGE DISTRIBUTIONS IN NUCLEAR COLLECTIVE MODES - Flaiyh, G N (Al-Nahrain Journal of Science, 2018)
An Expression for the transition charge density is investigated where the deformation in nuclearcollective modes is taken into consideration besides the shell model transition density. The inelasticlongitudinal form factors C2 are calculated using this transition charge density with excitation ofthe levels in 10B (J ,T) : f (1 0)  at Ex =0.718 MeV, (1 0) at Ex =2.154 MeV, (2 0)  atEx =3.587 MeV, (3 0)  at Ex =4.774 MeV, (2 0)  at Ex =5.920 MeV and (4 0) at Ex =6.025MeV. In this work, the core polarization transition density is evaluated by adopting the shape ofTassie model togther with the derived form of the ground state two-body charge densitydistributions (2BCDD’s). It is noticed that the core polarization effects which represent thecollective modes are essential in obtaining the remarkable agreement between the calculatedinelastic longitudinal F(q)’s and those of experimental data.